Custom-made sulfonated poly (ether sulfone) nanocomposite proton exchange membranes using exfoliated molybdenum disulfide nanosheets for DMFC applications. (4th July 2018) - Divya, Kumar; Sri Abirami Saraswathi, Meenakshi Sundaram; Rana, Dipak; Alwarappan, Subbiah; Nagendran, Alagumalai
Abstract: Exfoliated molybdenum disulfide (E-MoS2 ) incorporated sulfonated poly ether sulfone (SPES) nanocomposite proton exchange membranes (PEMs) were made by solution casting method. E-MoS2 was synthesized from bulk MoS2 powder by ultrasonication and SPES was prepared by sulfonation of PES using sulfuric and chlorosulfonic acid. Surface characterization of these membranes have been performed using several techniques such as Fourier transformed infra-red spectroscopy, x-ray diffraction, atomic force microscopy, scanning electron microscopy and contact angle measurements. In order to assess the physicochemical performance of the membranes, water uptake, swelling ratio and ion exchange capacity (IEC) of the membranes were measured. Thermal and mechanical stability of the nanocomposite PEMs were probed by thermogravimetric, analysis and tensile strength measurement respectively. Physicochemical characteristics such as water uptake, IEC, swelling ratio, thermal and mechanical stability of SPES/E-MoS2 nanocomposite PEMs were increased upon comparison with the bare SPES PEM. Tensile strength of SPES-1 nanocomposite PEM (117 MPa) is doubled upon comparison with pure SPES PEM (60 MPa). AFM images of PEMs nanocomposite revealed that surface roughness and nodular size were increased upon the addition of E-MoS2 . Electrochemical performance of nanocomposite membranes such as proton conductivity, selectivity and methanol permeability were investigated and results confirmed that SPES/E-MoS2 nanocomposite membranes exhibited better performance than bare SPES PEM. More specifically, SPES membrane incorporated with 1 wt% E-MoS2 (SPES-1) exhibited higher proton conductivity (3.17 × 10 −3 Scm −1 ), selectivity (8.43 × 10 4 Scm −3 s) and lower methanol permeability (0.376 × 10 −7 cm 2 s −1 ). From the results, it is evident that SPES-1 PEM nanocomposites are better candidate for applications in DMFCs. Graphical abstract: Image 1 Highlights: High proton conducting and methanol resistant SPES/E-MoS2 nanocomposite PEMs were effectively fabricated. SPES-1 PEM exhibited higher proton conductivity and selectivity whereas lower methanol permeability. SPES/E-MoS2 nanocomposite PEMs were found appropriate and promising for use in DMFCs.